2015
DOI: 10.1523/jneurosci.0169-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Specification of Cortical Subcerebral Projection Neurons Depends on the Direct Repression of TBR1 by CTIP1/BCL11a

Abstract: The acquisition of distinct neuronal fates is fundamental for the function of the cerebral cortex. We find that the development of subcerebral projections from layer 5 neurons in the mouse neocortex depends on the high levels of expression of the transcription factor CTIP1; CTIP1 is coexpressed with CTIP2 in neurons that project to subcerebral targets and with SATB2 in those that project to the contralateral cortex. CTIP1 directly represses Tbr1 in layer 5, which appears as a critical step for the acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 56 publications
2
49
1
Order By: Relevance
“…Hevner et al () also reported ER81 expression in corticospinal neurons, while Harb et al (2016) indicated that ER81 + cells are solely callosal projection neurons. Given that Ctip2 is expressed mostly in subcortical projection neurons, our ER81 + Ctip2 + cells in layer 5 of S1 may include corticospinal and corticocollicular neurons in line with the report by Arlotta et al (), while ER81 + Ctip2 ‐ cells may include callosal neurons (Canovas et al, ). In contrast to these reports, Dehorter et al () suggests that the majority of ER81 cells is interneurons, mostly expressing parvalbumin but also somatostatin, in layer 2/3 of mouse SCx.…”
Section: Discussionsupporting
confidence: 89%
“…Hevner et al () also reported ER81 expression in corticospinal neurons, while Harb et al (2016) indicated that ER81 + cells are solely callosal projection neurons. Given that Ctip2 is expressed mostly in subcortical projection neurons, our ER81 + Ctip2 + cells in layer 5 of S1 may include corticospinal and corticocollicular neurons in line with the report by Arlotta et al (), while ER81 + Ctip2 ‐ cells may include callosal neurons (Canovas et al, ). In contrast to these reports, Dehorter et al () suggests that the majority of ER81 cells is interneurons, mostly expressing parvalbumin but also somatostatin, in layer 2/3 of mouse SCx.…”
Section: Discussionsupporting
confidence: 89%
“…Our model of Ctip1 function is at odds with that of Cánovas et al (Cánovas et al, 2015), who recently proposed that CTIP1 is extensively co-expressed with CTIP2 and is a positive control over SCPN development through repression of TBR1. In direct contrast, we demonstrate that expression of TBR1 and other characteristic CThPN genes is reduced in the absence of Ctip1 (Figure 3G–L, Figure 4M–O), and that expression of CTIP2 is increased (Figure 3A–B), leading to more early-born neurons becoming SCPN (Figure 4A–F).…”
Section: Discussioncontrasting
confidence: 80%
“…Mutations in TBR1 are associated with intellectual disability and ASD, and functional implications will likely impact its activity as a transcriptional regulator, its cellular localization or its interaction with co-regulators. Complex interactions of several genes with Tbr1 determine the corticothalamic projection of layer VI neurons, callosal projection of neurons in the cortical superficial layers [335] and subcortical projection of layer V neurons [50, 142, 232]. Tbr1 in turn regulates the expression of rostrocaudal and layer-specific markers in the cerebral cortex, the former being partly through activation of the autism gene AUTS2 [28].…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%